HUBUNGAN BUDAYA ORGANISASI DENGAN KINERJA - Hasan Muzaki; Priyo Anggoro (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
This research is entitled The Relationship between Organizational Culture and Performance at FE UNUGHA Cilacap. From the results of the author's observations and research, it can be concluded that Organizational Culture and performance are two things that are interrelated with one another. In general, organizational culture and performance at FE UNUGHA still need improvement in various fields. Among them are the quality and effectiveness of the performance of each lecturer. Apart from that, in organizational culture, communication patterns between leaders and lecturers still need to be optimized.